Time to analgesia and pain score documentation best practice standards for the Emergency Department – A literature review. Issue 1 (February 2016) - Hatherley, Claire; Jennings, Natasha; Cross, Rachel
Summary: Background: Emergency Department pain management is an often overlooked aspect of acute care and is of paramount importance. Patients are often forced to wait extended periods of time without pain assessment or being offered analgesia for their painful condition. This has been associated with poor psychological and physiological consequences both for the health system and the patient. This is suggestive of a lack of clarity around best practice standards for time to analgesia and pain score documentation in the ED. Methods: A literature review was undertaken to investigate best practice in relation to acute pain management. Key outcomes were pain score documentation and time to analgesia. After a search of the electronic databases, a total of 992 abstracts were screened and 38 potentially relevant full articles were reviewed. There were 23 articles excluded for a variety of reasons including poor methodology, indirect specialty and inappropriate focus or age of study. A total of 15 studies were appropriate for inclusion in the review. Results: Of the 15 studies, only eight included pain score as an outcome and 13 used time to analgesia as a measure. Four studies specifically investigated nurse initiated analgesia programs in relation to improving acute pain management. A higher incidence of pain assessment, reassessment and pain score documentation was generally correlated with decreased time to analgesia. Conclusions: Whilst there is an abundance of evidence available on the current practice and challenges of quality acute pain management in the ED, there is a lack of well-controlled studies on best practice standards for health care services to benchmark their practice and improve. Mandating pain score reporting, pain assessment and reassessment within specific timeframes and analgesia administration within 30 min of arrival is highly recommended. The implementation of nurse led analgesia protocols should be encouraged to increase incidence of documented pain assessment and reduce time to analgesia.